Neosporosis: An Overview of Its Molecular Epidemiology and Pathogenesis. (February 2020) - Khan, Asis; Shaik, Jahangheer S.; Sikorski, Patricia; Dubey, Jitender P.; Grigg, Michael E.
Abstract: Neospora caninum ( N. caninum ), a cyst-forming protozoan parasite, is a major cause of bovine abortions and neonatal mortality worldwide. N. caninum has a broad intermediate host range, and its sexual cycle occurs exclusively in canids. Another species of Neospora, Neospora hughesi ( N. hughesi ), has been identified and causes myeloencephalitis in horses. Although molecular epidemiology studies are in their infancy, the 18S ribosomal RNA (rRNA) and ITS1 regions within the small subunit ribosomal RNA (ssuRNA) and an N. caninum species-specific DNA probe (pNc5) have been used extensively to differentiate Neospora from other closely related apicomplexan parasites. While these repetitive regions have higher sensitivity and specificity than housekeeping or antigen genes, they suffer from low discriminatory power and fail to capture intra-species diversity. Similarly, although multiple minisatellite or microsatellite marker studies have shown clear geographic substructures within Neospora, strains are often misclassified due to a convergence in the size of different alleles at microsatellite loci, known as homoplasy. Only one strain, N. caninum Liverpool (Nc-Liv), has been genome sequenced and compared with its closest relative, Toxoplasma gondii ( T. gondii ). Hence, detailed population genomics studies based on whole-genome sequences from multiple strains worldwide are needed in order to better understand the current population genetic structure of Neospora, and ultimately to determine more effective vaccine candidates against bovine neosporosis. The aim of this review is to outline our current understanding of the molecular epidemiology and genomics of Neospora in juxtaposition with the closely related apicomplexan parasites Hammondia hammondi and T. gondii .